Design of Lightning Protection for Multi-Storey Buildings at the Malikussaleh University Rectorate Building - Putri, Raihan; Isra, Raihan; Salahuddin, Salahuddin; Muhammad, Muhammad; Askarov, Rafael; Abdullah, Ahmad Zaidi bin (LPPM Universitas Andalas, 2025)
The Malikussaleh University Rectorate Building is a multi-storey building that is facilitated for academic and bureaucratic activities. It is necessary to safeguard against natural conditions such as lightning which may occur in the building area, including the contents of the building in the form of many electronic equipment connected to electricity such as computers, television, radio, CCTV, telephone and various other electronic equipment. Based on data received from the Meteorology, Climatology and Geophysics Agency (BMKG), 393 lightning strikes occurred in North Aceh, especially the Reuleut area, from February to May 2023. Building protection can be determined based on calculations calculated using several subclassifications of the General Installation Regulations Lightning Distribution (PUIPP). based on the level of need according to the PUIPP standard with a value of R=16, NFPA with a value of R=22, and IEC 1024-1-1 value of E= 95% with level II protection. The design of the lightning rod follows the PUIPP Standard by using a type, namely an air termination system with the brand